Containerizing solution based on Kubernetes of database and its cluster - Liyun YAN; Zhenwei HE; Xinzhang YANG; Ling ZHANG; Shaoxin HOU (Dianxin kexue)
With the maturity of container technology,more and more internet companies and IT companies have begun to migrate their core business platforms to the container environment.After more than three years of rapid development,Kubernetes has become the industry's preferred container cluster management platform.The containerization scheme of MySQL database and its cluster was given from the perspective of database containerization,based on the analysis of the key technology of database containerization on Kubernetes.Through the evaluation and comparison of performance and reliability of various database models,problems that database containerization technology may encounter and suggestion of database container hosting scheme under different scenarios were proposed.